2023
DOI: 10.1051/epjconf/202327703003
|View full text |Cite
|
Sign up to set email alerts
|

Electron temperature fluctuation levels of the quasi-coherent mode across the plasma radius

Abstract: EDA H-mode is an ELM-free regime in which the edge quasi-coherent mode (QCM) replaces the ELMs. The estimated location of the quasi-coherent mode is in a partly optically thin region of steep gradients localized between ρpol = 0.96 -1. Relative fluctuations of radiation temperature between 15 and 80 kHz are about 7% with significant density contribution. In the electron cyclotron emission (ECE) channels with resonances in the plasma core, a mode with the same frequency as the quasi-coherent mode is measured. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…In both regimes a characteristic edge fluctuation is prominent, called the quasi-coherent mode (QCM), being a known signature of the EDA H-mode [10,19,20], and, as shown here, is also linked to the mode shown by Griener et al [16] and Wolfrum et al [21] in the QCE regime. At Alcator C-Mod, Theiler et al [22] has shown, using the gas puff imaging diagnostic that the QCM moves in ion diamagnetic direction with frequency f ≈ 86 kHz, is localized near the E r minimum and has a poloidal wavenumber of k θ ≈ 1.9 cm −1 .…”
Section: Introductionsupporting
confidence: 67%
“…In both regimes a characteristic edge fluctuation is prominent, called the quasi-coherent mode (QCM), being a known signature of the EDA H-mode [10,19,20], and, as shown here, is also linked to the mode shown by Griener et al [16] and Wolfrum et al [21] in the QCE regime. At Alcator C-Mod, Theiler et al [22] has shown, using the gas puff imaging diagnostic that the QCM moves in ion diamagnetic direction with frequency f ≈ 86 kHz, is localized near the E r minimum and has a poloidal wavenumber of k θ ≈ 1.9 cm −1 .…”
Section: Introductionsupporting
confidence: 67%